A presença brasileira na América do Sul: ações e instrumentos de política externa - Santos, Marcelo [UNESP] (My University, 2013)
In this paper, the performance of Brazilian foreign policy in South America during the governments of Lula da Silva (2003-2010) and Rousseff (2011-2014) is discussed. It is showed that this activity has expanded in areas of greater consensus in the internal and external contexts. Thus, although with contradictions, initiatives to implement the infrastructure integration of transport, communications and energy into a political project, expansion of the role of the BNDES in the region and improvement of regional technical cooperation have been increasing.

Este texto envolve uma reflexão sobre a atuação da política externa brasileira na América do Sul nos governos Lula da Silva (2003-2010) e Dilma Rousseff (2011-2014). Argumenta-se que essa atuação tem se expandido em esferas que possuem maiores consensos nos planos interno e externo, daí os avanços, não sem contradições, nas iniciativas de tornar a integração da infraestrutura de transporte, comunicações e energia em projeto político, na ampliação do papel do BNDES na região e no incremento da cooperação técnica regional.
The Brazilian presence in South America: Actions and instruments of foreign policy
Keywords: Brazilian foreign policy; South America; Regional Cooperation; BNDES; IIRSA; Política externa brasileira; América do Sul; Cooperação Regional; BNDES; IIRSA